A novel LC‐MS/MS method for determination of tissue distribution and excretion of timosaponin B‐II in rat biological matrices. (17th December 2013) - Xu, Zhongyuan; Gao, Shouhong; Cai, Fei; Zhang, Feng; Jiang, Wei; Liu, Xiaowei; Chen, Wansheng
ABSTRACT Timosaponin B‐II (TB‐II) is a natural bioactive steroid glycoside extracted from the Chinese medicinal herb Anemarrhena asphodeloides Bge. (Fam. Liliaceae). It has been demonstrated to have a good anti‐inflammatory effect and a low bioavailability (1.1%). Clinical research has focused on developing it into a completely new medicine. In this study, a rapid and sensitive analytical method based on LC‐MS/MS has been developed for the determination of TB‐II in rat biological matrices (tissues, bile, urine and feces samples). The analytes and internal standard were isolated from 100 μL samples by solid‐phase extraction and then separated using a DIKMA Inertsil ODS‐3 column (5 µm, 2.1 × 150 mm) with an isocratic mobile phase consisting of acetonitrile–0.05% formic acid (35:65) at a flow rate of 0.25 mL/min. Calibration curves (1/χ2‐weighted) offered satisfactory linearity (r2 ≥ 0.990) within the test range. The accuracy, precision, recoveries and matrix effects were satisfactory in all the biological matrices examined. The assay was successfully applied to a tissue distribution and excretion study in rats. The preclinical data are useful for the design of clinical trials of TB‐II. Copyright © 2013 John Wiley & Sons, Ltd.